O PORÓWNANIACH W JĘZYKU JÓZEFA KORZENIOWSKIEGO (NA PRZYKŁADZIE PORÓWNAŃ Z ŁĄCZNIKIEM JAK W POWIEŚCI „SPEKULANT”) - Żurawska-Chaszczewska , Jowita (Studia Europaea Gnesnensia, 2018)
The article is a contribution to the series of studies which investigate the idiostyle of Józef Korzeniowski, including the analysis of similes in 14 works by the writer. The author examines comparative constructions with conjunctions as/like in Korzeniowski’s first novel and distinguishes grading and non-grading comparative statements, as well as textual and associative ones; comparandum and comparatum are also discussed.